1998
DOI: 10.1046/j.1432-1327.1998.2540090.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of two cDNAs encoding three small serine protease inhibiting peptides from the desert locust Schistocerca gregaria and analysis of tissue‐dependent and stage‐dependent expression

Abstract: This study describes the cloning of two cDNAs encoding three serine-protease-inhibiting peptides, SGPI I, II and III, which were recently identified from ovarian extracts of the desert locust, Schistocerca gregaria. The first cDNA codes for the precursor polypeptides of SGPI I and SGPI II; the second encodes only a single inhibitor, SGPI III. Northern-blot analysis revealed an approximate length of 0.8 kb for SGPI-I/II mRNA and 0.6 kb for SGPI-III mRNA. The transcripts are present in several locust tissues, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Important changes in transcript levels occur during development. Vanden Broeck et al also provided evidence indicating that the expression of the inhibitors is hormonally regulated [55]. cDNA cloning revealed two isoforms of a novel pacifastin-related precursor in Schistocerca gregaria, SGPP-3, which codes for three putative inhibitor peptides, two novel peptides (SGPI-4A en C) and a peptide (SGPI-4B), which most likely corresponds to the earlier purified SGPI-4.…”
Section: The Pacifastin Family: Precursor Genesmentioning
confidence: 97%
See 1 more Smart Citation
“…Important changes in transcript levels occur during development. Vanden Broeck et al also provided evidence indicating that the expression of the inhibitors is hormonally regulated [55]. cDNA cloning revealed two isoforms of a novel pacifastin-related precursor in Schistocerca gregaria, SGPP-3, which codes for three putative inhibitor peptides, two novel peptides (SGPI-4A en C) and a peptide (SGPI-4B), which most likely corresponds to the earlier purified SGPI-4.…”
Section: The Pacifastin Family: Precursor Genesmentioning
confidence: 97%
“…Similarly, SGPI-1 and SGPI-2 are derived from a single polypeptide precursor in Schistocerca gregaria [55], called Schistocerca gregaria pacifastin-related precursor-1 or SGPP-1, whereas SGPI-3 is encoded by an additional precursor, SGPP-2 [55]. The transcripts are present in several locust tissues, but not in the midgut.…”
Section: The Pacifastin Family: Precursor Genesmentioning
confidence: 99%
“…Gregarious desert locusts, S. gregaria (Forskål), were reared under crowded conditions according to the method previously described by Vanden Broeck et al (1998). Breeding of solitarious desert locusts was performed under isolated conditions as described by Hoste et al (2002).…”
Section: Rearing Of the Animalsmentioning
confidence: 99%
“…In order to compensate for possible variations due to pipetting errors and differences in reverse transcriptase efficiency, a S. gregaria b-actin transcript was analyzed as an endogenous control. Our previous studies indicated that the levels of this mRNA remain quite constant in locust tissues, regardless of developmental or physiological conditions (Vanden Broeck et al 1998, Janssen et al 2001, Claeys et al 2003. Primers for the endogenous control were described previously (Claeys et al 2005).…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…The most e$cient inhibitor of crayfish ppA is pacifastin which contains a light chain with nine proteinase inhibitor subunits and a heavy chain containing three transferrin lobes [70]. The molecule is held together by a peptide bond and forms a new class of proteinase inhibitors named pacifastin-like serine proteinase inhibitors and which are present in, and can inhibit the proPO system in many insects [71,72].…”
Section: Immune Responses In Invertebratesmentioning
confidence: 99%